A systematic study of Ichneumonosoma de Meijere, Pelmatops Enderlein, Pseudopelmatops Shiraki and Soita Walker (Diptera: Tephritidae) - Chen, Xiao-Lin; Norrbom, Allen; Freidberg, Amnon; Chesters, Douglas; Islam, Md Sajedul; Zhu, Chao-Dong (Zootaxa, 2015)
Four fruit fly genera, Ichneumonosoma de Meijere, Pelmatops Enderlein, Pseudopelmatops Shiraki and Soita Walker, were studied and 19 species are recognized. Three new species, Soita infuscata Chen & Norrbom, Ichneumonosoma quadripunctata Chen & Freidberg, and I. triangularis Chen & Norrbom are described and illustrated. Ichneumonosoma and Soita are revised, and keys to all the species are provided. Ichneumonosoma imitans (de Meijere) is newly recorded from Thailand. One new synonym is established: Soita Walker = Xaniosternum Enderlein, and Xaniosternum ophioneum Enderlein is moved from Xaniosternum to Soita (n. comb.). In addition, new morphological, geographic and biological information for two stalk-eyed fruit fly genera, Pelmatops and Pseudopelmatops, are provided. Pelmatops fukienensis Zia & Chen is newly recorded from Burma, Pelmetops ichneumoneus (Westwood) is newly recorded from Thailand and Burma, Pseudopelmatops angustifasciatus Zia & Chen is newly recorded from Vietnam, and the male of P. angustifasciatus is described and illustrated for the first time. The morphology of the compound eye and occipital protuberance of Pelmatops and Pseudopelmatops is described and illustrated for the first time. A cladistic analysis based on morphological characters of adults, a partial molecular analysis using the nuclear 28S rDNA (28S) and the mitochondrial cytochrome c oxidase I (COI) genes and a combined dataset were conducted to reconstruct the phylogeny of the four genera and their species. The results showed good support for monophyly of each of the four genera and the clade of the stalk-eyed fruit flies (Pelmatops + Pseudopelmatops). However, relationships of the stalk-eyed fruit flies with Soita and Ichneumonosoma are not clearly resolved, with the morphological analysis indicating that Ichneumonosoma is the sister group of the stalk-eyed fruit flies, but the 28S analysis and the combined analysis group Soita closer to the stalk-eyed fruit flies. Regarding relationships amongst congeners, Pelmatops was well resolved; Ichneumonosoma and Soita were partly resolved, and Pseudopelmatops was unresolved. In addition, a hypothesis about the biology of Pseudopelmatops and its relationship with Sesiidae (Lepidoptera) is discussed.